Termination of Criminal Investigations by The Prosecutor Under Criminal Law - Nurkholim Nurkholim (LEGAL BRIEF, 2021)
One of the functions of a sovereign state of law is to be able to properly administer each judicial process and realize it in a very broad scope of society. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that each country has its own way of completing each judicial decision as well as Indonesia as a country that is very obedient and obedient to applicable laws, the Indonesian people highly respect every judicial process that is carried out. issued through the prosecutor's decision, while the mechanism for terminating the decision of the prosecution of cases carried out by the attorney general is a special authority regulated through a law and has certain reasons for each decision making, as for several reasons that serve as a reference for prosecutors in implementing The judicial process includes cases that do not have strong enough evidence to be involved in a trial process, then the case has passed the time limit determined by the trial and lastly The case is closed for a legal interest, the purposes of the interests contained in the Act have a broad meaning and one of them concerns the interests of the state and society at large.